Lysosomal Storage Diseases-Regulating Neurodegeneration - Rob U. Onyenwoke; Jay E. Brenman (Journal of Experimental Neuroscience, 2015)
Autophagy is a complex pathway regulated by numerous signaling events that recycles macromolecules and can be perturbed in lysosomal storage diseases (LSDs). The concept of LSDs, which are characterized by aberrant, excessive storage of cellular material in lysosomes, developed following the discovery of an enzyme deficiency as the cause of Pompe disease in 1963. Great strides have since been made in better understanding the biology of LSDs. Defective lysosomal storage typically occurs in many cell types, but the nervous system, including the central nervous system and peripheral nervous system, is particularly vulnerable to LSDs, being affected in two-thirds of LSDs. This review provides a summary of some of the better characterized LSDs and the pathways affected in these disorders.